Le personnel est encore politique - Claude Chastagner (Caravelle)
Corridos, a popular musical genre among Mexican and Mexican-American populations, are part of a realistic aesthetic that for a long time made them vectors of social protest and resistance. In recent years, young artists on both sides of the border have been inflecting this poetic tradition with more intimate songs, approaching topics such as family, love, and even school, in a stimulating language, characterized by cultural code-switching. The songs of the Las Vegas-based group T3R Elemento will allow us to observe whether these new aesthetic approaches still constitute a form of protest and resistance. Is the revolutionary feminist slogan of the sixties, “personal is political”, still relevant today?